Building an Equitable Society in Colombia - World Bank (World Bank, Washington, DC, 2021)
Colombia’s high level of inequality is a core constraint to economic growth and social progress. The country has one of the highest levels of income inequality in the world, the second highest among 18 countries in Latin America and the Caribbean (LAC), and the highest among all OECD countries. The disparities in income across adults grow from gaps that open early in life in opportunities for high-quality childhood development, education, and health care services. Inequality in access to good jobs further amplifies these gaps, making Colombia among the countries where inequalities are the most persistent across generations. Longstanding inequality across regions overlaps with the large gaps in welfare between Afro-descendants and indigenous Colombians and the rest of the population. The COVID-19 pandemic has further amplified disparities and threatens to have prolonged negative effects, but this is just one of many potential extreme shocks, including climate change, related disruptions, that could substantially widen the inequality gaps. Current tax and transfer policies at best have only a modest positive impact on these imbalances, so there is clearly ample potential to improve the redistributive role of fiscal policy in Colombia. Policy reforms across many areas could help to chart a more equitable future for the country.